A new species and a revised of Sloanea cordifolia (Elaeocarpaceae) in China, southeast Yunnan - Xie, Yifei; Xie, Lei; Zhang, Zhixinag (Phytotaxa, 2018)
The taxonomic status of Sloanea cordifolia has been questionable as a variation of S. tomentosa by Coode. After field investigations, careful examination of herbarium specimens, the results showed that the flower of S. cordifolia is similar to S. tomentosa, and the difference between these two species is hair-related only. The statistical analysis revealed S. cordifolia and S. tomentosa clearly belong to the category of short prickles compared to species throughout the area; prick length of S. longiaculeatae is shorter compared to S. mollis, but the discontinuity is not particularly obvious; the width showed S. longiaculeatae is different from S. mollis, and S. cordifolia is larger than S. tomentosa. It is also the first time that the description of Sloanea cordifolia was completed. S. cordifolia K. M. Feng ex Hung T. Chang treated as Sloanea tomentosa (Benth.) Rehder & E.H. Wilson var. cordifolia (K. M. Feng ex Hung T. Chang) Y. F. Xie & Z. X. Zhang. The new species Sloanea longiaculeatae have been described and illustrated.